LncRNA ODRUL Contributes to Osteosarcoma Progression through the miR-3182/MMP2 Axis - Zhu, Kun-Peng; Ma, Xiao-Long; Zhang, Chun-Lin (Molecular therapy, 2017)
Recent findings have shown that lncRNA dysregulation is involved in many cancers, including osteosarcoma (OS). In a previous study, we reported a novel lncRNA, ODRUL, that could promote doxorubicin resistance in OS. We now report the function and underlying mechanism of ODRUL in regulating OS progression. We show that ODRUL is upregulated in OS tissues and cell lines and correlates with poor prognosis. ODRUL knockdown significantly inhibits OS cell proliferation, migration, invasion, and tumor growth in vitro and in vivo by decreasing matrix metalloproteinase (MMP) expression. A microarray screen combined with online database analysis showed that miR-3182 is upregulated and MMP2 is downregulated in sh-ODRUL-expressing MG63 cells and that miR-3182 harbors potential binding sites for ODRUL and the 3′ UTR of MMP2 mRNA. In addition, miR-3182 expression and function are inversely correlated with ODRUL expression in vitro and in vivo. A luciferase reporter assay demonstrated that ODRUL could directly interact with miR-3182 and upregulate MMP2 expression via its competing endogenous RNA activity on miR-3182 at the posttranscriptional level. Taken together, our study has elucidated the role of oncogenic ODRUL in OS progression and may provide a new target in OS therapy.